Place Making within an Urban Public Milieu: An Ethnographic Study of the New Dwellers in Butwal (Prithvi Journal of Research and Innovation, 2023)
This paper is based on research undertaken with the main objective of analyzing the modes of place making adopted by the new dwellers within an urban public milieu of Devinagar, Butwal. The data required were collected ethnographically using in-depth interviews, observations, and kuragraphy. The qualitative data analyzed manually have shown that the new dwellers from the rural origin find it chaotic initially but adapt to the urban milieu gradually by using the available public places. The Chautari [public resting place] of Devinagar Chowk, Devi Mandir [Hindu temple] and path [narrow street] and their chowks provide major avenue for adapting to the new socio-cultural context. Moreover, newer people tend to create their identity through the active as well as meaningful contribution in various public activities in their setting. This has eventually enabled them to produce a space of their own. Public places increase familiarity amongst newer and older dwellers and provide a perfect platform for social integration. The place making efforts maximize the dwellers’ chance to enhance their social position. This study shows that people use their financial, social, and other resources to the optimum for turning their place making efforts into a reality. The urban public places and situational junctures in Devinagar provide every dweller with equal chance to experience urban encounters. When these urban encounters occur repeatedly, the social integration process between newer and older dwellers strengthens. This study concludes that the new dwellers who are more skillful to map their opportunities are more successful in using public places more suitably, thereby turning their place making endeavors into a reality.